Motion Graphic Media Informasi Edukasi Penyakit Tuberculosis(TBC) Pada Klinik Karawaci Medika Tangerang - Gilang Kartika Hanum; Arif Purwadi; Putra Rizky Aupahaq (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
Tuberculosis or better known as TBC disease is a disease caused by the bacteria Mycobacterium Tuberculosis. This disease can be suffered by anyone, both young and old. Karawaci Medika Clinic, located in the Karawaci area of ​​Tangerang, is a clinic that provides health services for individuals and company employees by providing basic and / or specialist medical services. Karawaci Medika Clinic has handled various diseases, one of which is TBC. Currently, people do not know much about the spread and consequences of TBC disease so that the number of people affected by this disease continues to grow every year. The current TB information delivery at the Karawaci Medika Clinic is still using banners and brochures. The delivery media did not make the public interested in knowing information about TB. The community only read briefly and then threw away the brochures that had been given by the clinic. Based on the existing problems, a motion graphic video about TBC was made so that it could help the Karawaci Medika Clinic in conveying information about TB disease. The method used in making multimedia-based information media is data collection methods, media design and the concept of media production. The applications used in this research are Adobe Premiere pro CS6, Adobe After Effects CS6, Adobe Photoshop CS6, Adobe Audition CS6, and Adobe Media Encoder CS6. The final result is a video information motion graphic health education about TBC.